Effects of voluntary removal of ractopamine hydrochloride (Optaflexx) on live performance and carcass characteristics of beef steers. Issue 2 (9th March 2021) - Rincker, Phillip J; Allen, Janet B; Edmonds, Matt; Brown, Michael S; Kube, John C
Abstract: There is a lack of consistency across the globe in how countries establish tissue ractopamine residue limits and which residue limits are applied to various tissues, particularly for edible noncarcass tissues. Therefore, some U.S. beef slaughter organizations have recommended a 48-h voluntary removal of ractopamine before slaughter to meet residue requirements of specific export countries and maintain international trade. Our objective was to assess the impact of voluntary removal of ractopamine hydrochloride (Optaflexx; Elanco, Greenfield, IN) up to 8 d before slaughter on growth performance and carcass characteristics. Crossbred beef steers (60 pens of 10 animals/pen) with an initial shrunk body weight (BW ) of 611.8 ± 10 kg SEM were fed one of six treatments over 42 d. Treatments included a control that did not receive ractopamine, on-label use of ractopamine (0-d withdrawal), and 2, 4, 6, or 8 d of voluntary removal of ractopamine from feed before slaughter. The start of ractopamine feeding (30.1 mg/kg of diet dry matter for 32 d) was staggered, so that blocks could be slaughtered on the same day. Dry matter intake was decreased by 0.5 kg/d when ractopamine was fed with a 0-d withdrawal ( P = 0.04) compared with the control, but was not altered ( P = 0.56) as the duration of ractopamine removal increased from 0 to 8 d. Final BW, total BW gain, and average daily BW gain were increased by feeding ractopamine with a 0-d withdrawal ( P = 0.09) compared with the control, but these variables decreased in a linear manner ( P = 0.10) as the duration of removal increased from 0 to 8 d. Gain efficiency was improved by 15% ( P < 0.01) by feeding ractopamine with a 0-d withdrawal compared with the control, and gain efficiency decreased linearly ( P = 0.06) as the duration of ractopamine removal increased. Approximately 2/3 of the increase in gain efficiency remained after 8 d of removal. Hot carcass weight was increased by 6 kg ( P = 0.02) by feeding ractopamine with a 0-d withdrawal compared to the control. Measured carcass characteristics were not altered by ractopamine feeding or by removal before slaughter ( P ≥ 0.24). The consequences of voluntary removal of ractopamine up to 8 d before slaughter were a linear decrease in live BW gain (0.64 kg/d), poorer gain efficiency, and numerically lighter carcass weight.